A Kúria önkormányzati rendeleteket felülbíráló jogköre esetjogi megközelítésben - Bene, Enikő (Debreceni Jogi Műhely, 2016)
The Council of Self-Government Affairs of the Curia of Hungary, which was established in 2012, has the power to review judicial norms beside the Constitutional Court of Hungary in order to abolish the collision between them. The division between the issues of the collision is determined up on the fact whether the question is statutory or a constitutional. The specific interpretation of the Curia and its consistent, conceptual statements that have already been made, leads to the conclusion, that such an institution was created that is able to promote the autonomy of the legislation of self-governments in the right direction. This is the issue that I would like to focus in my paper the most, and to examine what are those most important and conceptual statements, which are also important from a practical perspective. I extended my observation particularly on the legal standards regulating the basic rules of coexistence, where I examined the standards in respect of the most common dilemmas from a case-lawpoint of view.